Penerapan Framework CodeIgniter dalam Sistem Informasi Pengelolaan Jadwal Video Conference (VICON) Polrestabes Palembang - Mita Tri Murtiningsih; Fatmasari Fatmasari (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Abstract Today, the exchange of information can be made not only by text or by voice but also by video. This is a video conference. Polrestabes Palembang is an institution that is affected by the covid-19 and has not yet been computerized in video conferences and in managing video conference schedules. The purpose of the study is to build information management systems for video conference schedules using the framework codeigniter and the software development method of the waterfall method. The waterfall method has five procedures, such as requirement analysis, design, implementation, testing, support and maintenance. The result of research is that the information system was successfully built using the framework codeigniter, which has three models: model, view, controller. The information system can manage the data for the video conference schedule that will be done and can do a video conference itinerary recaption as needed. Result of testing, all the menus on this information system can be used as desired.